Integrated care for older adults during the COVID‐19 pandemic in Belgium: Lessons learned the hard way. (11th February 2021) - Deschacht, Martha; Malfait, Simon; Eeckloo, Kristof
Abstract: The corona pandemic challenges countries worldwide in many different ways. Due to its magnitude and impact on global health, this health crisis exposes several shortcomings in their health systems and emphasizes their shortcomings and deficiencies. These deficiencies have quickly affected the most frail citizens, such as older people. The first wave of the COVID19 pandemic in Belgium has quickly shown that nursing homes were not prepared for these kinds of crises. The nature, speed and extent gave rise to an accelerated and more extensive collaboration between various nursing homes and Ghent University Hospital. Before this crisis, the level of integrated care between nursing homes and hospitals was mostly limited. But setting up a strong collaboration model and integrated care between nursing homes and hospitals enables the nursing homes to manage this specific and complex care in their own environment. Implications for practice: This case study shows that integrated care is possible and that both the hospital and the nursing homes benefit from such a system. Investments in people, resources, training and guidance concerning transitional care and knowledge exchange between hospitals and nursing homes, are necessary to guarantee a more efficient and robust approach to (pandemic) crises in nursing homes.